Solve for x 1 0 8 9 + ( 2 1 1 − 6 6 ) 1 0 8 9 + ( 2 1 1 − 3 3 ) 1 0 8 9 + 2 1 1 … = x
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Typo there in the identity on LHS! no x + 2 n , it should be x + n
It is a very easy problem, if you know " Ramanujan's Identity". But, how many people in the world will know " Ramanujan 's Identity".
Log in to reply
Didn't know Ramanujan's identity! But, still managed to solve it. :)
Most overrated (400 point) problem that I have solved on brilliant. This should be level-2 problem Anyways +1.
x=√{1089+(2^11-66)√{1089+(2^11-33)....
or, x^2-33^2 = (2^11-66)√{1089+(2^11-33)....
now it is clear that
(2^11-66)<√{1089+(2^11-33)....
so, x-33=2^11-66
x=2015
Problem Loading...
Note Loading...
Set Loading...
by Ramanujan identity, a x + ( n + a ) 2 + x a ( x + n ) + ( n + a ) 2 + ( x + n ) ⋯ ⋯ = a + x + n now insert a = 0 , x = 2 1 1 − 6 6 , n = 3 3 3 3 2 + ( 2 1 1 − 6 6 ) 1 0 8 9 + ( 2 1 1 − 3 3 ) 3 3 2 + 2 1 1 … = 3 3 + 2 1 1 − 6 6 = 2 0 1 5